Potenziale der Portfolioarbeit für den Aufbau vernetzten Wissens im Bachelorstudium: Eine Explorationsstudie im Studienfach Komparatistik/Vergleichende Literatur- und Kulturwissenschaft - Hannebohm, Ronja (die hochschullehre: Interdisziplinäre Zeitschrift für Studium und Lehre)
Vernetztes Wissen ist ein zentrales Lernziel des Hochschulstudiums, insbesondere im interdisziplinär angelegten Studienfach Komparatistik. Um den Aufbau vernetzten Wissens bei Bachelorstudierenden der Komparatistik zu unterstützen, ist in diesem Projekt Portfolioarbeit eingesetzt worden, die als Methode selbsttätigen und selbstreflexiven Lernens geeignet erscheint, zur Auseinandersetzung mit Lerninhalten zu motivieren und zur Kompetenzentwicklung der Studierenden beizutragen. Mittels unstrukturierter Beobachtungen der Portfolioarbeit im Seminar sind inhaltliche Effekte und methodische Entwicklungen erfasst worden. Anhand anteilig quantitativer, überwiegend qualitativer Inhaltsanalysen der Portfolios sind konkrete Vernetzungen zwischen Lerninhalten ermittelt worden. Die Explorationsstudie zeigt veränderte Perspektiven und geweckte Interessen bei den Studierenden durch die Portfolioarbeit sowie vielfältige Kontextualisierungen, Vergleiche und Verknüpfungen in den Portfolios auf und bietet hierdurch einen möglichen Ansatzpunkt für strukturelle Empfehlungen für das Studienfach Komparatistik.
Keywords: Portfolioarbeit; portfolio work; vernetztes Wissen; knowledge networks; Beobachtung; naturalistic observation; Inhaltsanalyse; content analysis

Kurzfilme als Kommunikations-, Kompensations-, Diskurs- und Inter-/Intramedien. Eine kritische Kurzfilmhermeneutik für den Religionsunterricht - Karsch, Manfred; Keuchen, Marion; Weber, Astrid (TheoWeb. Zeitschrift für Religionspädagogik)
Der Beitrag untersucht Kurzfilme als Kommunikations-, Kompensations- und Diskursmedien im Religionsunterricht und entwickelt eine kritische Kurzfilmhermeneutik. Ausgangspunkt ist die Beobachtung, dass Kurzfilme im Unterricht häufig inhaltlich verengt und primär als Mittel zur Themenvermittlung genutzt werden. Demgegenüber betonen die Autor:innen die spezifische Ästhetik, Mehrdeutigkeit und mediale Komplexität des Kurzfilms. Zentrale Kategorien sind dabei das Zusammenspiel von „story“ und „discourse“ sowie inter-, intra- und transmediale Bezüge. Kurzfilme eröffnen durch Verdichtung, Leerstellen und offene Enden eigenständige Zugänge zu Sinnfragen und fördern aktive Rezeptionsprozesse. Anhand des Films „YELLOW“ wird gezeigt, wie filmische Gestaltungselemente Bedeutung generieren und gesellschaftlich-religiöse Diskurse anstoßen. Eine kritische Kurzfilmhermeneutik erweitert somit die Filmdidaktik, indem sie das Medium selbst stärker in den Fokus rückt. Ziel ist eine reflektierte, medienkompetente und dialogorientierte Nutzung von Kurzfilmen im Religionsunterricht.
Keywords: Film; Religionsunterricht; Fachdidaktik; Hermeneutik

Nach 1984: Biopoethik des eugenetischen Romans - Hannebohm, Ronja
Was bedeutet es, ‚Mensch‘ zu sein im Zeitalter des entschlüsselten Genoms? Der eugenetische Roman ist als ein literarisches Genre zu begreifen, das biowissenschaftliche, bioethische und biopoetische Dimensionen miteinander verbindet, um ebendiese Frage auszuloten und hierbei Grenzen und Konstanten des Mensch(lich)en auszuhandeln. Mindestens seit Darwin und Galton sind die Modifizierung des menschlichen Individuums und die Optimierung der menschlichen Spezies diskutiert worden, spätestens seit den 1980er Jahren haben humangenetische und biotechnologische Entwicklungen den Diskurs neu perspektiviert. Literatur trägt zu diesem Diskurs bei, indem sie Erprobungs- und Reflexionsräume schafft: Sie modelliert menschliche Subjekte, die in eugenetische Zukunftsszenarien eingeschrieben sind, und entwickelt spezifische Erzählweisen, die diese Subjekte, ihre Lebensweisen und ihr Lebenswissen narrativ erfahrbar machen. Fünf eugenetische Romane der englisch- und deutschsprachigen Gegenwartsliteratur von Margaret Atwoods „The Handmaid’s Tale“ (1985) bis Emma Braslavskys „Leben ist keine Art, mit einem Tier umzugehen“ (2016) werden in der Studie hinsichtlich Subjektmodellierungen und Narrationsweisen im Kontext der Eugenetik untersucht.
Keywords: Ethik; Eugenik; Genre; Lebenswissen; Macht; Metamoderne; Narration; Postmoderne; Subjekt; Zukunft

Skills Help, but They Don’t Help All at Once: Changes in the Relationship Between Study- Relevant Skills and Student Stress as Well as Study Satisfaction During the First Two Years of Teacher Education - Sagolla, Nils; Seifert, Andreas; Bohndick, Carla; Buhl, Heike M. (Journal for Educational Research Online)

Ongoing efforts to enhance stability - Keller, Adrian Clemens (Nucleic Acid Insights)
Over the last few decades, a large variety of nucleic acid‑based therapeutic approaches and drug formulations have been developed in the lab, tested in the clinic, and brought to market, ranging from antisense oligonucleotides (ASOs) and siRNAs to aptamer inhibitors and mRNA vaccines, with DNA and RNA nanostructure therapeutics already looming on the horizon. However, being susceptible toward hydrolysis, oxidation, non‑specific binding, and nuclease digestion, unmodified nucleic acids are rapidly degraded in vivo, resulting in poor therapeutic performance. Therefore, several stabilization strategies have been developed in order to protect those fragile molecules against adverse conditions during storage and in the body, while simultaneously accommodating their various mechanisms of action such as cellular uptake, target binding, or translation. These strategies include chemical modifications at the nucleoside level, complexation with proteins and polymers, and encapsulation in lipid nanoparticles (LNPs). Despite this variety of available methods, the field still faces many challenges, and this issue aims to provide an overview of the ongoing efforts to enhance the stability of therapeutic nucleic acids.

Digging to the Ground Truth: Solving Multi-objective Gray-Box Optimization Problems through Hyperplane Elimination - Mensendiek, Carolin; Preuß, Oliver Ludger; Rook, Jeroen; Chicano, Francisco; Whitley, Darrell; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2026, Centro Internacional de Convenciones CIC-ANDE, San Jose, Costa Rica, July 13-17, 2026)

Partner models of explainers: a qualitative interview study - Gladow, Viviane; Buhl, Heike M. (Frontiers in Education)

Conceptualising Risk and Risk Literacy—results of a Delphi Study Konzeptualisierung von Risiko und Risikokompetenz – Ergebnisse einer Delphi-Studie - Eichler, Andreas; Büchter, Theresa; Binder, Karin (Journal für Mathematik-Didaktik)
Abstract Risk is an integral part of modern societies and therefore school education, and in particular mathematics education, should develop students’ risk literacy. Students’ risk literacy is part of the interdisciplinary research project siMINT (Understanding complex STEM topics: Using simulations to promote competences for the 21st century). One first challenge in this project was to find a common ground for the inconsistently conceptualised terms of risk and risk literacy. Consequently, the aim of this paper is to contribute to the conceptualisation of risk and risk literacy. The first part of this paper provides a literature review on these areas, resulting in a working conceptualisation of the two concepts. We further carried out two consecutive steps of a Delphi study with N = 15 and N = 12 experts respectively, to develop a common conceptualisation based on the plurality of different dimensions and elements of risk and risk literacy. Based on the results of the first step of the Delphi study, we modified our working conceptualisation, using a common model of risk and risk literacy with different dimensions. In the second step of the Delphi study, the experts comment on (i) the dimensions and (ii) the elements of risk and risk literacy in these dimensions. The results showed that the experts are able to locate their individual definitions of risk in the model with three dimensions (relation between risk/uncertainty, connotation, and mathematical object) that we developed and to formulate reasons for their allocation. Furthermore, the results revealed that risk literacy consists of subsets of mathematical and non-mathematical elements that the experts rate differently with regard to their importance. In general, the results contribute to clarifying the constructs of risk and risk literacy as a basis for developing approaches to improve risk literacy.

Evaluation des Buddy-Programms der GDCP-Jahrestagung 2025 - Zwick, Linda; Bühler, Eva; Weiler, David Christoph (KI in der naturwissenschaftlichen Bildung)
Der Erfolg von Wissenschaftler:innen in frühen Karrierephasen (WiKa) hängt von vielen Faktoren ab, wobei die wissenschaftliche Gemeinschaft ein entscheidender Faktor sein kann (Cornér et al., 2018; Corceslles et al., 2019; Corcelles-Seuba et al., 2023). Vor diesem Hintergrund ist es wichtig, dass die wissenschaftliche Gemeinschaft gezielte Unterstützungsangebote für WiKa bereitstellt, in denen sie neben dem fachlichen Austausch auch Möglichkeiten zur Vernetzung und sozialen Unterstützung haben. Die WiKa der GDCP haben 2023 mit dem Buddy-Programm auf der Jahrestagung begonnen, um Wissenschaftler:innen zu Beginn ihrer Promotionszeit ein strukturiertes Unterstützungsangebot bereitzustellen. Das Buddy-Programm wurde in den folgenden Jahren basierend auf den Rückmeldungen der Teilnehmenden weiterentwickelt. In diesem Beitrag werden die Evaluationsergebnisse des Buddy-Programms während der Jahrestagung 2025 vorgestellt und diskutiert.
Keywords: GDCP; Buddy-Programm; Evaluation

The integration of probability-based arguments in risk-related contexts - Büchter, Theresa; Binder, Karin; Eichler, Andreas (Proceedings of the IASE 2025 Satellite Conference - Statistics and Data Science Education in STEAM)

Simulationen in der MINT-Bildung - Impulse für den Mathematikunterricht (Der Mathematikunterricht)

The role of social-emotional competencies for children’s cooperative learning processes in inclusive primary school classrooms. Individual Oral Presentation. 5th Porto International Conference on Research in Education (ICRE) 2026. - Hellmich, Frank; Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Oral Presentation. 5th Porto International Conference on Research in Education (ICRE) 2026. - Löper, Marwin Felix; Hellmich, Frank

Unterschiedliche Typen von Simulationen - Klassifikation, Beispiele und unterrichtlicher Einsatz - Büchter, Theresa; Binder, Karin; Eichler, Andreas (Der Mathematikunterricht)

Entwicklung einer wärmebildkamerabasierten Temperaturmesseinrichtung im Lasersinterverfahren - Azam, Mohammad Hamid

Early postural dynamics reveal the rapid processing of fake social cues for deceptive actions in sports - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Schmidt, Thomas; Weigelt, Matthias (Scientific Reports)
Abstract Deceptive actions such as head fakes are a hallmark of interactive sports, yet it is not well understood how decisions and whole-body responses to head fakes unfold over time. In the present study, participants viewed video sequences of a basketball player passing to the left or right, either with or without a head fake. In the buzzer task, participants moved laterally to press a response button as if to intercept the pass. In the vocal task, they verbally indicated pass direction. Reaction times (RTs), movement times (MTs), and medio-lateral center-of-pressure (CoP) displacements were recorded to investigate whether motor output is rapid and stimulus-driven or rather requires continuous integration of fake and pass cues. Further, we investigated whether the mere observation of a basketball player leads to overt micromovements even if no response movement is intended. The data analysis shows that head fakes increased RTs in both the buzzer and vocal tasks. In the buzzer task, head fakes induced an initial, small erroneous CoP shift, which was then rapidly corrected. When CoP trajectories were aligned by head orientation, fake and non-fake trajectories diverged shortly after movement onset. In the present dynamic sport-related context, this pattern is more compatible with the early integration of head and pass information than with a strictly sequential prime-target account, although the paradigm differs from classic Rapid Chase Theory designs with discrete primes and target events. In the vocal task, participants were not instructed to move, yet CoP traces showed tiny but systematically lateralized micromovements with a temporal structure resembling that in the buzzer task, albeit without an initial erroneous shift for head fakes. These postural fluctuations are consistent with action-observation-related motor activation, although they do not uniquely identify motor resonance and may also reflect attentional or generalized embodied response tendencies. A clear deceptive response conflict at the postural level emerged only when a lateralized action was prepared.

Global solutions and large time stabilization in a model for thermoacoustics in a standard linear solid - Black, Tobias; Winkler, Michael (Evolution Equations and Control Theory)

Krise oder Rekonfiguration? - Scharlau, Ingrid (Forschung und Lehre)

Characterization of spatial Schmidt modes in high-gain SU(1,1) interferometers - Scharwald, Dennis; Sharapova, Polina (Physical Review Research)
Multimode quantum light has promising applications in many areas of physics, such as quantum communications and quantum computing. However, its multimode nature also makes it challenging to measure its properties. Recently [I. Barakat et al., Optica Quantum 3, 36 (2025)], a technique for the simultaneous measurement of squeezing of multiple broadband modes based on a phase-sensitive amplification approach was experimentally implemented using a setup that effectively corresponds to an SU(1,1) interferometer. Here, we aim to provide a complete theoretical analysis of the modal structure of (generally unbalanced) SU(1,1) interferometers and a detailed theoretical formal derivation of the framework for this technique. Utilizing the joint Schmidt decomposition of the transfer functions, we investigate the shape and phase profiles of the modes of the SU(1,1) interferometer and its components [parametric down-conversion (PDC) sections] for different parametric gain regimes. We discover a complicated interplay between the PDC modes and the modes of the entire interferometer, and analyze it by using their overlap coefficients as a similarity measure. Finally, we develop a rigorous processing method for the aforementioned multimode squeezing measurement technique and discuss necessary approximations to make this method experimentally feasible.

Professionalisierung angehender Lehrpersonen für Sprachbildung mittels Unterrichtsvideos. Eine qualitative Inhaltsanalyse von Studierendentexten - Dehn, Freya (die hochschullehre)